Protection of Geographical Indications as a Form of Consumer Rights Protection - Dian Ety Mayasari (Yuridika, 2019)
The potential of natural resources in a region that is well managed and provides economic benefits to the local communities deserves protection for geographical indications. It is part of intellectual property rights as it relates to the protection of the identities of producer regions that are affected by both human and natural factors. The provision of protection for geographical indications, that adopts a constitutive registration system, put emphasis on the potentials of the certain region because the distinctiveness of a product from the region cannot be found in the others. The protection of geographical indications granted for an unlimited period of time protects not only the producer regions but also the reputation, quality, as well as characteristics of their products. To provide protection of geographical indications means also to protect the consumer rights; consumers that purchase or use certain products are supplied with correct information on the production sites, quality and being protected from the potentially harmful effect of the products.